An investigation of molecular interactions between zinc phthalocyanine thin film and various oxidizing gases for sensor applications - Rawat Jaisutti (2018)
Molecular interaction between zinc phthalocyanine (ZnPc) thin films and various oxidizing gas molecules was examined by measuring sensor response of chemiresistor structures. The different response types can be obtained from the interactions to gas molecules of nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ) and carbon monoxide (CO). For NO 2 interaction, the response current of thermal evaporated ZnPc thin film with metal inter-digitaged pattern electrodes was proportionally increase to the concentration of NO 2 gas. For measurement cycle, the NO 2 gas at desired concentration was flowed into the measuring chamber for 20 minutes then the nitrogen gas was flowed for 20 minutes to recovering the interaction. The current response exhibited the step up and down during this measuring cycle and the heights of response step were proportional to the NO 2 concentration. For SO 2 measuring cycle, the response step increased at the beginning cycle then the response of ZnPc thin film seemed to be saturate and remained the same response step height even increasing the SO 2 concentration. It was found that if the SO 2 concentration was maintained at the same value for each measuring period, the response current was increase for the first few cycles after that the response step height decreased and became almost constant at lower value after passing more than ten measuring cycles. However this phenomenon can recover if the ZnPc surface was leaved in air for a few days. Therefore the interaction between ZnPc and SO 2 molecules can modify the ZnPc surface and change the gas response. With the same measurement setup, it cannot found any significant change in the response current of the ZnPc film under the CO gas exposure up to concentration of 250 ppm. This result indicated that no interaction between ZnPc and CO molecules can be observed and these different responses on various gas molecules can demonstrate the selectivity of using ZnPc as a gas sensor. © (2012) Trans Tech Publications, Switzerland.